Trans-free vanaspati containing ternary blends of palm oil-palm stearin-palm olein and palm oil-palm stearin-palm kernel olein - Nor Aini, I.; Che Maimon, C. H.; Hanirah, H.; Zawiah, S.; Che Man, Y. B. (Wiley, 1999)
Four samples of trans-free vanaspati were made using palm oil-palm stearin-palm olein (PO-POs-POo) blends (set A) and another four samples (set B) using palm oil-palm stearin-palm kernel olein (PO-POs-PKOo). Palm stearin iodine value [iodine value (IV), 30] and soft palm stearin (IV, 44) were used in this study. The products were evaluated for their physical and chemical properties. It was observed that most of the vanaspati were granular (grainy) and had a shiny appearance. Chemical analyses indicated that vanaspati consisting of PO-POs-POo had higher IV (47.7-52.4) than the PO-POs-PKOo vanaspati (37.5-47.3). The higher IV demonstrated by set A samples was due to their higher content of unsaturated fatty acids, 46.0-50.0% compared to 36.6-45.0% in set B. Decreasing the amount of palm oil while increasing palm stearin in the formulations resulted in higher slip melting points and higher yield values. Eutectic interaction was observed in PO-POs-PKOo blends. The β′ crystalline form was predominent in PO-POs-POo samples (set A). One formulation in set B exhibited β crystallinity. From the differential scanning calorimetry thermograms, samples in set B showed a high peak at the low-melting region as well as a high peak at the high-melting region. In set A, the peak at the low-melting region was relatively lower.